2022
DOI: 10.3390/medicina58081101
|View full text |Cite
|
Sign up to set email alerts
|

Does Multisystem Inflammatory Syndrome Only Mimic Acute Appendicitis in Children or Can It Coexist: When Should We Suspect MIS-C?

Abstract: Background and Objectives: Acute abdominal pain in children has been noticed to be a primary reason to seek medical attention in multisystem inflammatory disorder (MIS-C), which can prevail separately or together with acute appendicitis. Our aim was to distinguish regular appendicitis cases from MIS-C and to suggest the best clinical and laboratory criteria for it. Materials and methods: Cases of patients, admitted to the Pediatric Surgery Department over a six-month period in 2021, were retrospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Vansevičienė et al 27 aimed to distinguish regular appendicitis cases from MIS-C and to suggest the best clinical and laboratory criteria for this differentiation; they found that MIS-C can be suspected even when clinical data and performed tests suggest AA.…”
Section: Discussionmentioning
confidence: 99%
“…Vansevičienė et al 27 aimed to distinguish regular appendicitis cases from MIS-C and to suggest the best clinical and laboratory criteria for this differentiation; they found that MIS-C can be suspected even when clinical data and performed tests suggest AA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rapid progression of symptoms is against ischemia. Vansevičienė et al have suggested in cases presenting with acute appendicitis, CRP level higher than 55.8 mg/dL, presence of symptoms for longer than three days, and involvement of other organ systems hints to underlying MISC (12).…”
Section: Case Presentationmentioning
confidence: 99%